Hospital descrlptlve epidemiology of cerebrovascular disorders in G. Almenara 1. Natlonal Hospital - Deza, Luis (1989)
We present an epidemiological approach of a two years clinical observation study of a cohort of 208 admissions with cerebrovascular disease. This report represents part of a wider project intended to clarify the natural history of cerebrovascular diseases in Peru. We found a 70.7% of occlusions or stenosis, a 26.9% of intracerebral hemorrhages, a 1.9% of subarachnoid hemorrhage and a 0.5% of other unspecified. A mean age of onset of 62.2 years, with a very large range, probably with a later age in the cases o occlusion or stenosis - 63.9% - If we compare it with the cases of intracerebral hemorrhage, 58.1%. A general mortality percentage of 16.3, being much higher in intracerebral hemorrhage (37.5%) than in occlusions or stenosis (8.8%). A survival, in the mortal cases, of 27.2 days for occlusions or stenosis and 9.9 days for intracerebral hemorrhages. Our findings show some particular aspects of the natural history of cerebrovascular disorders in our country, some of them close to reports obtained from Asian countries (An Fac Med UNMSM II Epoca 1989; 1 (1-2) 31-34).